Learning from the past twenty years - Patti Kristjanson speaks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
CCAFS Patti Kristjanson talks about what lessons have been learned from the last twenty years. Interview with Patti Kristjanson (CCAFS). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya